2020
DOI: 10.1101/2020.04.03.024638
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The spectral sensitivity ofDrosophilaphotoreceptors

Abstract: 14Drosophila melanogaster has long been a popular model insect species, due in large part to 15 the availability of genetic tools and is fast becoming the model for insect colour vision. Key 16 to understanding colour reception in Drosophila is in-depth knowledge of spectral inputs 17 and downstream neural processing. While recent studies have sparked renewed interest in 18 colour processing in Drosophila, photoreceptor spectral sensitivity measurements have yet 19 to be carried out in vivo. We have fully char… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 30 publications
0
26
0
Order By: Relevance
“…1A). This specialized array of polarization detectors covers the complete 180° range of orientations and, with a peak spectral sensitivity to UV light, is well-suited to sensing the patterns of polarized light in the sky (Feiler et al, 1992;Salcedo et al, 1999;Sharkey et al, 2020;Weir et al, 2016). A previous characterization of DRA R7/R8 in Drosophila established the spatial organization of their tunings, and their visual response properties (Weir et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…1A). This specialized array of polarization detectors covers the complete 180° range of orientations and, with a peak spectral sensitivity to UV light, is well-suited to sensing the patterns of polarized light in the sky (Feiler et al, 1992;Salcedo et al, 1999;Sharkey et al, 2020;Weir et al, 2016). A previous characterization of DRA R7/R8 in Drosophila established the spatial organization of their tunings, and their visual response properties (Weir et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…These connectivity patterns suggest roles in circadian entrainment and learning and memory, respectively (Figure 11Bii). Drosophila pale R8 cells are most sensitive to blue wavelengths (Sharkey et al 2020; Salcedo et al 1999; Schnaitmann et al 2018; Heath et al 2020), and the projections of aMe12 and ML-VPN1 demonstrate that blue light is processed and used by the central brain within one synapse. Little is known about the central processing of color in Drosophila (Longden 2016), but the detection of blue light plays an important role in the circadian avoidance of bright light (Lazopulo et al 2019).…”
Section: Resultsmentioning
confidence: 99%
“…This was further demonstrated by the ERG responses to long (red) wavelengths. Recent work in Drosophila has shown that photopigments provide a mechanism for flies to detect orange and red wavelengths 32 , and it is possible that similar processes play a role in mosquitoes.…”
Section: Discussionmentioning
confidence: 99%